PERANCANGAN APLIKASI AUGMENTED REALITY SEBAGAI PENGENALAN GEDUNG KAMPUS KEPADA CALON MAHASISWA BARU DI UNIVERSITAS MUHAMMADIYAH PONOROGO - Rico Agus Prasetyo; Ghulam Asrofi Buntoro; Moh Bhanu Setyawan (Universitas Muhammadiyah Ponorogo, 2019)
Universitas Muhammadiyah Ponorogo is a well-known campus in the district of Ponorogo. From various regions in the Madiun residency many people are familiar with the Muhammadyah Ponorogo University campus. There are also many other campuses that are socialized to schools in various ways to promote their campuses. This research resulted in an Augmented Reality application as an introduction to the Android-based Campus Building Muhammadiyah Ponorogo. The purpose of this application is to support the development of technology and also facilitate campus PMB in socializing Ponorogo Muhammadiyah University Campus to prospective new students and can be operated anywhere by the user. Users of this system can see images of campus buildings in 3D virtuosity and building information. This application was successfully run on an android smartphone and successfully presented campus information.